The Effect of Teams Games Tournament (TGT) and Student Teams Achievement Divisions (STAD) Teaching Techniques on The Learning Outcome of Natural Science Subject - Mahdalena Permatasari; Dadang Kurnia; R. Teti Rostikawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2018)
The Effect of Teams Games Tournament (TGT) and Student Teams Achievement Divisions (STAD) Teaching Techniques on the Learning Outcome of Natural Science Subject to the students of fifth grade at V SDN Cijujung 03 Kecamatan Bogor. The research employs quasi experimental method and it shows that the average score of the class using TGT gets 7.4% with the N-gain of 1.26 and the class using Student Teams Achievement Divisions gets 5.7% with N-gain of 1.02. The T-tailed score significance or 0.000.05 or Ha is accepted. It can be inferred that there is a significant effect of using TGT and STAD on natural science subject of class 5 at SDN Cijujung 03 in the district of Bogor, the academic year of 2014-2015.